Impact of Counseling Received by Adolescents Undergoing Voluntary Medical Male Circumcision on Knowledge and Sexual Intentions. (3rd April 2018) - Kaufman, Michelle R; Patel, Eshan U; Dam, Kim H; Packman, Zoe R; Van Lith, Lynn M; Hatzold, Karin; Marcell, Arik V; Mavhu, Webster; Kahabuka, Catherine; Mahlasela, Lusanda; Njeuhmeli, Emmanuel; Seifert Ahanda, Kim; et al.
Abstract: Background: Little is known regarding the impact of counseling delivered during voluntary medical male circumcision (VMMC) services on adolescents' human immunodeficiency virus (HIV) knowledge, VMMC knowledge, or post-VMMC preventive sexual intentions. This study assessed the effect of counseling on knowledge and intentions. Methods: Surveys were conducted with 1293 adolescent clients in 3 countries (South Africa, n = 299; Tanzania, n = 498; Zimbabwe, n = 496). Adolescents were assessed on HIV and VMMC knowledge-based items before receiving VMMC preprocedure counseling and at a follow-up survey approximately 10 days postprocedure. Sexually active adolescents were asked about their sexual intentions in the follow-up survey. Prevalence ratios (PRs) and 95% confidence intervals (CIs) were calculated by modified Poisson regression models with generalized estimating equations and robust variance estimators. Results: Regarding post-VMMC HIV prevention knowledge, older adolescents were significantly more likely than younger adolescents to know that a male should use condoms (age 10–14 years, 41.1%; 15–19 years, 84.2%; aPR, 1.38 [95% CI, 1.19–1.60]), have fewer sex partners (age 10–14 years, 8.1%; age 15–19 years, 24.5%; aPR, 2.10 [95% CI, 1.30–3.39]), and be faithful to one partner (age 10–14 years, 5.7%; age 15–19 years, 23.2%; aPR, 2.79 [95% CI, 1.97–3.97]) to further protect himself from HIV. Older adolescents demonstrated greater improvement in knowledge in most categories, differences that were significant for questions regarding number of sex partners (aPR, 2.01 [95% CI, 1.18–3.44]) and faithfulness to one partner post-VMMC (aPR, 3.28 [95% CI, 2.22–4.86]). However, prevention knowledge levels overall and HIV risk reduction sexual intentions among sexually active adolescents were notably low, especially given that adolescents had been counseled only 7–10 days prior. Conclusions: Adolescent VMMC counseling needs to be improved to increase knowledge and postprocedure preventive sexual intentions.